The effects of Aronia berry (poly)phenol supplementation on arterial function and the gut microbiome in middle aged men and women: Results from a randomized controlled trial. Issue 11 (November 2022) - Le Sayec, Melanie; Xu, Yifan; Laiola, Manolo; Gallego, Fabiola Alvarez; Katsikioti, Daphne; Durbidge, Chandler; Kivisild, Uku; Armes, Sarah; Lecomte, Manon; Fança-Berthon, Pascale; Fromentin, Emilie; Plaza Oñate, Florian; et al.
Summary: Background and Aims: Berry (poly)phenol consumption has been associated with cardioprotective benefits, however little is known on the role the gut microbiome may play on such health benefits. Our objective was to investigate the effects of aronia berry (poly)phenol consumption on cardiometabolic health and gut microbiome richness and composition in prehypertensive middle-aged men and women. Methods: A total of 102 prehypertensive participants were included in a parallel 12-week randomized double-blind placebo-controlled trial. Volunteers were randomly allocated to daily consume an encapsulated (poly)phenol-rich aronia berry extract (Aronia, n = 51) or a matched maltodextrin placebo (Control, n = 51). Blood pressure (BP) and arterial function (office and 24 h), endothelial function (measured as flow-mediated dilation), serum biochemistry (including blood lipids), plasma and urine (poly)phenol metabolites as well as gut microbiome composition through shotgun metagenomic sequencing were monitored over the study period. Relationships between vascular outcomes, (poly)phenol metabolites and gut microbiome were investigated using an integrated multi-levels approach. Results: A significant improvement in arterial indices measured as augmentation index (AIx) and pulse wave velocity (PWV) was found in the Aronia compared to Control group (awake Δ PWV = −0.24 m/s; 95% CI: −0.79, −0.01 m/s, P < 0.05; 24 h peripheral Δ AIx = −6.8; −11.2, −2.3, %, P = 0.003; 24 h central Δ AIx = −3.3; −5.5, −1.0, %, P = 0.006). No changes in BP, endothelial function or blood lipids were found following the intervention. Consumption of aronia (poly)phenols led to a significant increase in gut microbiome gene richness and in the abundance of butyrate-producing species such as Lawsonibacter asaccharolyticus and Intestinimonas butyriciproducens species, compared to Control group. Results from an approach including metabolomic, metagenomic and clinical outcomes highlighted associations between aronia-derived phenolic metabolites, arterial stiffness, and gut microbiome. Conclusions: Aronia berry (poly)phenol consumption improved arterial function in prehypertensive middle-aged individuals, possibly via modulation of gut microbiome richness and composition based on the associations observed between these parameters. Clinical trial registry: The National Institutes of Health (NIH)-randomized trial records held on the NIH ClinicalTrials.gov website (NCT03434574). Aronia Berry Consumption on Blood Pressure .